Interfaith Cooperation between Muslims and Christians in the Construction of Side-by-Side Houses of Worship in Tanah Karo. - Br Ginting, Dina Anjani; Irwansyah, Irwansyah (Riwayat: Educational Journal of History and Humanities, 2024)
This article aims to demonstrate that there is cooperation between Muslim and Christian communities in the construction of places of worship side by side in Karo land. The research uses a qualitative method with a descriptive approach and data collection through observation and interviews. This study not only discusses the collaboration between Muslims and Christians in the process of constructing places of worship but also delves deeper into the factors driving the success of this cooperation. The results show that throughout the process of constructing a mosque and a church from start to finish, there was cooperation between Muslims and Christians. This can be evidenced by each phase of the construction process: planning, government coordination, fundraising, physical construction, and completion. Behind the success of this cooperation between Muslims and Christians, there are two driving factors that enabled the creation of inclusive collaboration: the factor of solidarity within the community and the factor of religion. The success of building two places of worship side by side, separated only by a wall, is an extraordinary achievement. The cooperation between Muslims and Christians, marked by determination and discipline, has achieved a common goal. Despite religious differences, they can live together harmoniously.